LIFELONG LEARNING AS A PREMISE FOR BUILDING THE LEARNING ORGANIZATION IN THE ROMANIAN SMES - Mironescu, Roxana; Feraru, Andreea; Drob, Catalin (Studies and Scientific Researches. Economics Edition, 2014)
To become more competitive, the SMEs in our study should encourage learning at all the organizational levels, meaning becoming learning organizations. The lifelong learning has become a vital necessity of the contemporary society, it is a theoretical principle and it acts to describe a specific reality of our century. The lifelong education should not be conceived as a mere preparation for life but as an important dimension, a continuous existential one, whose duration is overlapped with the life span. This research aims to capture the boundaries, inside the SMEs, where the organizational culture acts as an impulse for learning. The used investigation method was based on the findings and attitudes revealed by a questionnaire survey, on a systematic observation upon the phenomena and from the synthesis of some previous studies in this area. The paperwork emphasizes the importance of the strategic orientation towards knowledge management, stressing that the main advantage that such an economic entity as a SME can have is the ability to systematically and continuously exploit the obtained knowledge. The organizational learning may be even a means to achieve certain strategic objectives.